Is export-led growth a mirage? The case of Kenya - Peter Wamalwa; Maureen Were (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The role of exports in promoting economic growth has been widely acknowledged. This paper analyses the link between exporting and growth performance in Kenya using time series data. Despite trade liberalization and export promotion policies pursued over time, Kenya's export growth has been sluggish and its contribution to economic growth is still limited. Notwithstanding diversification efforts, exports are still strongly geared towards primary agricultural goods. Whereas the empirical results indicate a positive long-run relationship between exporting and output, the impact of exporting on output growth is found to be statistically insignificant in the short run. Nonetheless, analysis using disaggregated export data shows a statistically significant impact of manufactured exports on economic growth. The empirical results also indicate that compared to exports, imports have a relatively significant influence on short-run and long-run output growth. This signifies the import-dependent nature of the economy. There is a need to revamp export-led growth through enhanced competitiveness and value-addition avenues such as regional and global value chains.
Keywords: F1; F13; F14; 330; trade; export-led growth; imports; import substitution; Kenya